Frequency of Various Clinico-pathological Variants of Cutaneous Tuberculosis - Siddiqi, Muneebah; Ashraf, Erum; Devi, Vinesha; Shareef, Faryal; Abowath, Misbah Zakir; Hanif, Madiha (Indus Journal of Bioscience Research, 2025)
Background: Cutaneous tuberculosis falls into the category of rare extrapulmonary tuberculosis manifestations which occur throughout the world. The multiple clinical-pathological versions of this condition require diagnosis through histopathological examination. Objective: This study aimed to determine the frequency of various clinico-pathological variants of CTB in patients presenting to a tertiary care hospital. Methods: Researchers assessed patients at the Dermatology Department of Civil Hospital, Karachi during six months starting from April 20, 2018 to October 20, 2018. The researchers included fifty patients who received CTB diagnosis after getting approval from the ethical board and patient consent. For CTB variant diagnosis medical experts conducted history acquisition alongside clinical assessment while performing histopathological examinations. Results: Fifty patients comprised the sample group with 25 males and 25 females divided equally and had an average age of 42.90 ± 12.59 years. Scrofuloderma appeared as the primary clinico-pathological form of tuberculosis (21 cases, 42%) while lupus vulgaris (13 cases, 26%) stood as the second most observed variant and tuberculosis verrucosa cutis (10 cases, 20%) along with tuberculids (6 cases, 12%) followed as the remaining types. Conclusion: The clinical form scrofuloderma presented most often in CTB patients while lupus vulgaris, tuberculosis verrucosa cutis and tuberculids appeared less frequently. Proper diagnosis together with management of CTB demands extensive clinical analysis combined with pathological findings since CTB can exist alongside systemic tuberculosis. Timeous detection along with better understanding between medical professionals remains essential for avoiding serious CTB outcomes.